2017
DOI: 10.1111/eip.12471
|View full text |Cite
|
Sign up to set email alerts
|

The role of a family history of psychosis for youth at clinical high risk of psychosis

Abstract: There is a possibility that CHR + FH individuals believe that it is more difficult for them to cope with circumstances such as abuse or potential abuse. Future research on this subject should investigate family environment and its role in conversion to psychosis among CHR + FH individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…In contrast to most, but not all (Georgopoulos et al, 2019), studies comparing youth with and without family histories of psychotic disorders (Bora et al, 2014;Hemager et al, 2018), we found that youth with and without family histories of PS symptoms performed similarly on neurocognitive tests. However, after adjusting for PRS-S in the European-American subsample, we did find that FHPS status was associated with a small social cognition deficit and a small complex cognition deficit (at the trend level).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to most, but not all (Georgopoulos et al, 2019), studies comparing youth with and without family histories of psychotic disorders (Bora et al, 2014;Hemager et al, 2018), we found that youth with and without family histories of PS symptoms performed similarly on neurocognitive tests. However, after adjusting for PRS-S in the European-American subsample, we did find that FHPS status was associated with a small social cognition deficit and a small complex cognition deficit (at the trend level).…”
Section: Discussioncontrasting
confidence: 99%
“…The psychosis risk calculator variables included age at baseline, number of undesirable stressful life events (Research Interview Life Events Scale) (41), trauma history (Childhood Trauma and Abuse Scale) (42), sum of SIPS items P1 and P2 (unusual thought content and suspiciousness, respectively, rescored to range from 0 to 3, with non-prodromal severity levels rescored to 0), verbal learning (Hopkins Verbal Learning Test-Revised, sum of trials 1-3) (43), processing speed (Brief Assessment of Cognition in Schizophrenia, symbol coding test), past-year decline in social function (Global Functioning: Social) (44), and family history of psychotic disorders in first-degree relatives (Family Interview for Genetic Studies) (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…This review identified four studies specifically assessing whether PR individuals perceive discrimination in the society because of their condition (Georgopoulos et al, 2019; Rusch et al, 2014a; Saleem et al, 2014; Uttinger et al, 2018) (Table 1). All of them indicate that discrimination plays an important role in the experience of a PR state.…”
Section: Resultsmentioning
confidence: 99%
“…All of them indicate that discrimination plays an important role in the experience of a PR state. Also, two have a control group, specifically comparing (i) PR individuals with and without a family history of psychosis (Georgopoulos et al, 2019) and (ii) PR individuals and healthy subjects with reference to multiple sources of stigma other than mental health such as appearance, age, gender, ethnicity, skin color, religion, disability, and sexual orientation (Saleem et al, 2014). Another study is not analytic (Uttinger et al, 2018) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation